2018
DOI: 10.1016/j.jid.2017.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Nevus-Associated Cutaneous Melanoma: A Case-Case Study

Abstract: A proportion of cutaneous melanomas display neval remnants on histologic examination. Converging lines of epidemiologic and molecular evidence suggest that melanomas arising from nevus precursors differ from melanomas arising de novo. In a large, population-based study comprising 636 cutaneous melanomas subjected to dermatopathology review, we explored the molecular, host, and environmental factors associated with the presence of neval remnants. We found that nevus-associated melanomas were significantly assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…NAM usually appears in younger patients than de novo melanoma (DNM), with multiple nevi and in intermittently sun‐exposed skin areas as the trunk or extremities, as it occurs in our work. According to some authors, personal history of NAM is the most important risk factor to have another NAM, so this group of patients may benefit even more of digital dermoscopic follow‐up.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…NAM usually appears in younger patients than de novo melanoma (DNM), with multiple nevi and in intermittently sun‐exposed skin areas as the trunk or extremities, as it occurs in our work. According to some authors, personal history of NAM is the most important risk factor to have another NAM, so this group of patients may benefit even more of digital dermoscopic follow‐up.…”
Section: Discussionsupporting
confidence: 53%
“…The most frequent histologic subtype of NAM is superficial spreading melanoma, as well as in our series. Some works point out that NAM usually has lower Breslow depth, stage and the biopsy of sentinel lymph node is more often negative . However, this data should be interpreted with caution, as thicker NAM could mask the nevus remnants as it grows involving them and therefore being misdiagnosed as DNM.…”
Section: Discussionmentioning
confidence: 95%
“…It included 16,180 cases and reported similar nevi counts associated with melanoma of each histological subtype, without heterogeneity among RRs: 1.31 and 1.32 for NM and SSM, respectively (although NM was not directly compared to SSM) (7). Interestingly, higher nevus counts have been associated with thinner melanoma (8,9), better survival rates independently of Breslow thickness (8) and, more recently, with melanoma associated histologically with a nevus (10). A previous age-stratified study reported that for individuals younger than 60 years, the presence of more than 50 total nevi was associated with thinner melanoma, although the histological subtype was not investigated (9).…”
Section: Discussionmentioning
confidence: 99%
“…In both adults and children, new naevi can develop and existing naevi can regress. 5–7 Melanomas often grow adjacent to, or in some cases, within pre-existing naevi 8 and naevi are the major differential diagnosis of primary melanoma. 9 Therefore, improved understanding of naevus development and recognition of the importance of changes over time is key to understanding melanoma development and will help establish more efficient prevention and early detection models for melanoma.…”
Section: Introductionmentioning
confidence: 99%